(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The application of pragmatic theories, particularly Dewey’s views, in pedagogy has brought about significant transformations in educational systems worldwide. However, in the case of Iran, the implementation of pragmatist theories in education has faced various challenges. This paper examines the Iranian educational system, focusing on the obstacles hindering the application of pragmatist theories for children aged 8-12. It explores the characteristics of pragmatist theories and analyzes three dimensions of the Iranian educational structure: (1) defining childhood, child marriage, and child labor; (2) the social backgrounds of education in Iran; and (3) the educational facilities necessary for effective pedagogy. The conclusions highlight political factors and the absence of a robust educational model as the main barriers to realizing pragmatist pedagogy for Iranian children aged 8-12.